2003
DOI: 10.1046/j.1365-2389.2003.51318.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Prevent Aspiration Pneumonia in Older Adults: A Systematic Review

Abstract: A systematic review was conducted to assess the effectiveness of the following interventions for prevention of aspiration pneumonia (AP) in older adults: compensatory strategy/positioning changes, dietary interventions, pharmacologic therapies, oral hygiene, and tube feeding. Data sources included a key word search of the MEDLINE, EMBASE, Cochrane Library, CINAHL, and HealthSTAR databases and hand searches of six journals. Reference lists of relevant primary and review articles were searched. Studies included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 29 publications
0
91
0
1
Order By: Relevance
“…Oral microorganisms have been implicated in bacterial endocarditis, aspiration pneumonia, and other systemic diseases 1,2) . Especially, the morbidity caused by aspiration pneumonia has been recognized as a major geriatric health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Oral microorganisms have been implicated in bacterial endocarditis, aspiration pneumonia, and other systemic diseases 1,2) . Especially, the morbidity caused by aspiration pneumonia has been recognized as a major geriatric health problem.…”
Section: Introductionmentioning
confidence: 99%
“…They increase in direct relation with age and underlying diseases. The risk of aspiration pneumonia is higher in older patients because of the high incidence of dysphagia (Loeb et al 2003). In elderly nursing home residents with oropharyngeal dysphagia, aspiration pneumonia occurs in 43-50% during the first year, with a mortality of up to 45% (Cook and Kahrilas 1999).…”
Section: Respiratory Complications: Aspiration Pneumoniamentioning
confidence: 99%
“…In addition, there are a limited number of studies addressing these-unresolvedquestions. A recent review found that there are insufficient data to determine the effectiveness of treatments for dysphagia prevention in older adults (Loeb et al 2003). In contrast, other authors found that treatment of dysphagia is cost-effective and the use of dysphagia-preventive programs is correlated with a reduction in aspiration pneumonia rates (Logemann 1995).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Japanese investigators randomized 184 nursing home residents to intense oral care versus 182 controls. 60 Care consisted of brushing and/or wiping mucosal surfaces after each meal, sometimes with povidone iodine, as well as weekly cleaning by a hygienist.…”
Section: Preventionmentioning
confidence: 99%